Waste Management in Cities of India Need Introduction of Modular Concept for Sustainable Solutions - Prasad, Mahesh (AMC Indian Journal of Civil Engineering, 2022)
Waste Management in major cities in India is generally a grey area that needs proper attention. The rapid growth in population in cities caused due to mass influx of rural population in search of employment and better living and also the fast changing living standard in various strata of society are some of the major factors which are rendering even a properly planned scheme to a stage of inadequacy in a very short span of time. A scheme on waste management by the time it is physically implemented on ground is found to become under capacity, facing deficiencies all over places. Whether it is solid waste management or Waste Water Management, the issue of under design and need of augmentation is a common problem being faced on the ground. In such situations of rapid expanding dimensions of problems, introduction of Modular Concept in design of schemes can be more effective and convenient in design, implementation, and subsequent augmentations in phases. Solid waste management which is basically on the principle of 6 R i.e., Recycle, Reduce, Reuse, Repair, Re-gift, and Recover, can be planned and designed on a modular basis for a population of 5000 to 10,000 and earmarking a zone of 100,000 sq. ft. as “Solid Waste Area” having various facilities for composting, incineration, plastic shredding facility, metal segregation cells, cell for electronic waste, and everything at a place to function in an organized manner. Such operations can be handled by RWAs collectively with necessary aids from municipal authorities and the government. Such modular units of waste handling can serve as a tool for local employment. The “Modular Concept” similarly can also be well applied to Waste Water Management for handling liquid waste from colonies of population of 5000 to 10,000. There are various methodologies for waste water treatments and waste water recycling depending on the nature of the waste, but out of the lot, use of RBC (Rotating Bio Contactors) is more appropriate for small/medium capacity which can be conveniently subjected to phase wise augmentation by adding additional modules time to time. The present concept for aggregating the waste and handling it to transport the entire waste, be it the solid waste or the liquid waste to a far corner of city area for purpose of centralised handling/treatment and disposal. This concept of centralised handling of large mass needs a re-look in the present scenario.